Efficacy and Safety of Combined Extracts of Cornus officinalis and Ribes fasciculatum for Body Fat Reduction in Overweight Women - Park, Eunkuk (J Clin Med, 2020)
Obesity is a medical condition that presents excessive fat accumulation with high risk of serious chronic diseases. The aim of this clinical trial is to investigate the anti-obesity effects of Cornus officinalis (CO) and Ribes fasciculatum (RF) on body fat reduction in Korean overweight women. A total of 147 overweight female participants enrolled in double-blinded clinical trial for 12 weeks and 76 participants completed the clinical study. Participants were treated with four CO and RF mixture (COEC; 400 mg per tablet) or four placebo tablets once a day. Obesity associated parameters (body weight, body mass index (BMI), waist circumference, waist-to-hip ratio, body fat percentage and body fat mass) and safety assessment were analyzed. After 12 weeks of COEC treatment, primary outcomes such as body fat percentage (0.76% vs. 0.01%; p = 0.022) and mass (1.1 kg vs. 0.5 kg; p = 0.049) were significantly decreased. In addition, the results were statistically significant between the COEC and placebo groups, strongly indicated that COEC had anti-obesity effects on overweight women. Secondary outcomes—including body weight, waist and hip circumference, waist-to-hip ratio, body mass index and computed tomography measurement of visceral fat area, subcutaneous fat area, total abdominal fat area and visceral-to-subcutaneous fat ratio—were reduced in COEC-treated group, but no statistical differences were found between the COEC and placebo groups. The safety assessment did not differ between the two groups. These results suggest that treatment of COEC extract reduces body fat percentage and mass in Korean overweight women, indicating it as a protective functional agent for obesity.